Bank Accounting and Audit - Urinov Komil (Genius Publishing Group, 2022)
The definitions of "Bank accounting and audit" and the significance of each are given in this article in order to maintain the relevance of the banking system for clients. It provides pertinent information on the financial system and substantiates the details provided using reliable sources and scholarly studies
Keywords: monetary system; banking system; auditor; bank